Saudi women driving: images, stereotyping and digital media. (February 2023) - Albawardi, Areej; Jones, Rodney H
This article examines the representations of Saudi women driving that circulated shortly after the lifting of the ban and considers the social, commercial and technological forces that helped to shape those representations . A corpus of images was collected from two international image banks – Getty and Shutterstock – as well as from a Google Image search. The images use Van Leeuwen's (2008) visual representation framework in Discourse and Practice: New Tools for Critical Analysis, paying particular attention to the similarities and differences between the images available in the image banks and those that were made prominent in the Google search. In addition, semantic metadata accompanying these images were also analysed in order to understand the linguistic constraints that had been put on searches for these images and the ontologies of the issue that they promoted. Finally, a more detailed analysis was performed on images that had been appropriated into different contexts such as news stories and advertisements to investigate how these images were adapted to support different political, cultural and commercial agendas. Findings suggest that images of Saudi women that circulated online internationally shortly after the lifting of the ban were mostly generic and decontextualized, creating simplified and trivialized depictions of gender relations and social change in the Kingdom. The analysis shows how commercial concerns which influence both the creation of stock images and the way they are taken up by news organizations and advertisers can sometimes have the effect of erasing the complexity of political events and reinforcing the very stereotypes they seem to be challenging.